Comparing measurements of head motion and centre of pressure for body sway induced by optic flow on a head-mounted display - Ashida, Hiroshi; Fujimoto, Kanon (Frontiers in Virtual Reality, 2022)
We compared two measures of visually induced body sway, head motion and centre of pressure (CoP), that were concurrently measured while observing optic flow on a head-mounted display (HMD). Head motion can be conveniently obtained with HMDs, but may have some different features from the conventional measure of CoP, given the complex joint structures of our body. We found that the responses were very similar except for the response gain, and we did not find any crucial difference both in time and frequency domains. Our results support the use of head motion as a potential predictor of the variability in body sway, at least in studies of visually guided postural control.